Raster‐scanned intensity‐controlled carbon ion therapy for mucosal melanoma of the paranasal sinus - Mohr, Angela; Chaudhri, Naved Sarwar; Hassel, Jessica C.; Federspil, Philippe A.; Debus, Jürgen (Head & neck, 2016)
Background - The purpose of this study was to evaluate the use of raster‐scanned intensity‐controlled carbon ion therapy (ICCT) in the treatment of mucosal melanoma of the paranasal sinus. - - Methods - P...